RANCANG BANGUN ANTENA MIKROSTRIP SIERPINSKI GASKETARRAY PENGUAT MODEM GSM PADA KENDARAAN MOBIL PRIBADI - M. Yasin Anwar; Dodi Setiabudi; Widya Cahyadi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
The modem is a device used to connect users to the Internet, GSM modem frequency allocation in Indonesia, 900-1800 Mhz. Disadvantages of GSM modem that is, less than the maximum speed internet access. To support the GSM modem performance authors will design and make microstrip antenna Sierpinski Gasket type who works at a frequency of 1.3 GHz. In the test antenna simulation results obtained return loss is 23.3823 dB, VSWR 1.1787 dB, gain 1.852 dBm. Tests using a VNA, get a return loss when the frequency of 1.093 GHz, return loss -10.68 dB, SWR 1.80 dB, and when the frequency of 1.543 GHz, return loss -15.38 dB, SWR 1.53 dB. At the time of the test in motion by using an antenna default GSM modem at a speed of 10 km/H uplink 32.66 Kbps and downlink 913.66 Kbps, at a speed of 20 Km/H uplink 56.76 Kbps and downlink 1.52 Mbps, a speed of 30 Km/H uplink 59.15 Kbps and downlink 1.69 Mbps. When using an antenna array is connected to a GSM modem, at a speed of 10 Km/H uplink 139.91 Kbps and downlink 4.36 Mbps, at a speed of 20 Km/H uplink 210.22 Kbps and downlink 7.26 Mbps, at a speed of 30 Km/H uplink 154.04 Kbps and downlink 5.11 Mbps. Keywords: Mikrostip Antenna Sierpinski Gasket, GSM Modem